The role of cold‐inducible RNA binding protein in cell stress response. Issue 11 (26th June 2017) - Liao, Yi; Tong, Lingying; Tang, Liling; Wu, Shiyong
Abstract : Cold‐inducible RNA binding protein (CIRP) was discovered after the cells were exposed to a moderate cold shock because its production was induced. Other cellular stresses such as ultraviolet light radiation and hypoxia also could increase its expression. Under stress conditions, CIRP could up regulate its own expression by self‐transcriptional activation of alternative promoters. After relocating into cytoplasm from nucleus, CIRP assists cells in adapting to novel environmental conditions via stabilizing specific mRNAs and facilitating their translation. It not only participates in anti‐apoptosis processes under mild hypothermia condition, but also protects cells from ultraviolet radiation and hypoxia induced senescence process. This article focuses on the possible mechanisms of its inducible expression, cytoprotective functions and carcinogenesis. In addition, extracellular CIRP has been shown to be a novel danger‐associated molecular patter (DAMP) member and is able to induce inflammatory response. Finally, based on the distinct roles of CIRP in intracellular and extracellular conditions, a possible model of CIRP‐mediated cell fate has been proposed.